Penerapan Konsep Sustainable Terhadap Industri Fashion Halal Ditinjau dari Perspektif Islam: Studi Kasus Usaha Jahit Wati - Ashari , Fara Sofia; Muhamma Arif; Reni Ria Armayani Hasibuan (PT Maju Malaqbi Makkarana, 2023)
This research aims to analyze the potential and obstacles in implementing the sustainable concept in the halal fashion industry from an Islamic perspective in Wati's sewing business. In the research the author used a descriptive method with a qualitative research type. Research data was collected using interviews, observation and documentation. The results of this research are that the wati sewing business has not implemented the sustainable concept in its business due to a lack of awareness and understanding of the sustainable concept. In the Islamic view, the application of the sustainable concept has a significant impact. As caliph on earth, Wati's sewing business manager has moral and ethical responsibilities in carrying out its operations. There are several strengths if the sustainable concept is applied to the wati sewing business, namely responsibility for the environment, opportunities for innovation, attractiveness for consumers and the wider market, and a pleasant work environment. However, there are also weaknesses, namely financial limitations, technological limitations, limited human resources and lack of training.